Health and safety aspects of textile workers from Solapur (India) textile industries - Hiremath, Rahul B; Kattumuri, Ruth; Kumar, Bimlesh; Hiremath, Gurudevi R (Indian Journal of Community Health, 2014)
Introduction: Textile sector in India plays an important role in the country's economy, providing employment to a significant population in rural and urban areas. Objectives: This paper focuses on health and safety aspects of textile workers in Solapur City (one of the key textile cluster) in the state of Maharashtra, India. Methodology: A sample of 180 workers from the identified textile industries of Solapur city were assessed for their general physique, muscle tone, lung condition, and eyesight using different techniques. The study aimed at developing a framework for understanding risks to textile workers resulting from lack of health and safety standards in companies. Results: Findings showed that most of the workers have been affected by respiratory problems, increase in muscle tone, eye problems and musculoskeletal problem. It has been also observed that job security or regular work impacts positively to the worker’s long term body health. However, there is an immediate need to adopt and implement measures in accordance with Indian Factories Act (OHSAS 18001/ILO-OSH 2001) which includes directions and procedures in respect of industrial installations, work environment and occupational health and safety guidelines.